2014
DOI: 10.5751/es-06907-190413
|View full text |Cite
|
Sign up to set email alerts
|

Generalizable principles for ecosystem stewardship-based management of social-ecological systems: lessons learned from Alaska

Abstract: ABSTRACT. Human pressure could compromise the provision of ecosystem services if we do not implement strategies such as ecosystem stewardship to foster sustainable trajectories. Barriers to managing systems based on ecosystem stewardship principles are pervasive, including institutional constraints and uncertain system dynamics. However, solutions to help managers overcome these barriers are less common. How can we better integrate ecosystem stewardship into natural resource management practices? I draw on exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…High performance in the conservation of dynamic systems requires the ability to respond fast to potentially emerging habitat discontinuities that could be detrimental to species being conserved. Our findings thus agree with many previous findings on the effective management of social-ecological systems, which highlight the importance of environmental monitoring (Cox 2012), adaptive capacity , Garmestani et al 2013, Allen et al 2016), cross-scale https://www.ecologyandsociety.org/vol22/iss2/art30/ interactions (Hansen 2014), and the utilization of landowners' knowledge (Olsson et al 2007, Green et al 2015 in the attainment of high institutional fit in these contexts.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…High performance in the conservation of dynamic systems requires the ability to respond fast to potentially emerging habitat discontinuities that could be detrimental to species being conserved. Our findings thus agree with many previous findings on the effective management of social-ecological systems, which highlight the importance of environmental monitoring (Cox 2012), adaptive capacity , Garmestani et al 2013, Allen et al 2016), cross-scale https://www.ecologyandsociety.org/vol22/iss2/art30/ interactions (Hansen 2014), and the utilization of landowners' knowledge (Olsson et al 2007, Green et al 2015 in the attainment of high institutional fit in these contexts.…”
Section: Resultssupporting
confidence: 82%
“…Fire management institutions (Richards et al 1999, Keeley and Fotheringam 2001, Stewart et al 2005) provide examples of institutions that aim at providing continuums of early successional habitats. Their design and performance have been studied from a spatially implicit perspective (Hansen 2014). …”
Section: Conservation Of Dynamic Habitat Networkmentioning
confidence: 99%
“…urban, GĂłmez-Baggethun and Barton, 2013;agricultural, Ango et al, 2014;forest, Agbenyega et al, 4 2009; and aquatic, Limburg et al, 2010). It has also been used for a diversity of purposes, in particular to understand people's perceptions (Teixeira et al, 2019), to identify bundles of ES and EDS (Campagne et al, 2018), to assess EDS-related financial costs (Mackenzie and Ahabyona, 2012) and to inform management in conservation areas (Hansen, 2014). Based on this empirical research, EDS conceptual frameworks and classifications have progressively gained substance (LyytimĂ€ki and SipilĂ€, 2009;Shackleton et al, 2016;Von Döhren and Haase, 2015).…”
Section: An Expanding Yet Understudied Conceptmentioning
confidence: 99%
“…While our review is not exhaustive, it does suggest that even though there are clear feedbacks between land use and fire, they are still often studied as a closed rather than coupled system. This may be changing however, as recent research has shown promise in this area [20,84,85]. We suggest that future research into fire and land use as a coupled system is necessary to provide pathways to a future where we co-exist with fire as a natural process, and when possible, better plan how and where we build.…”
Section: Discussionmentioning
confidence: 99%